Relationship between Coral Reefs and the Abundance of Reef Fish of the Pomacentridae Family in the Waters of Setan Island, West Sumatra - Wardana, Rangga; Thamrin, Thamrin; Rifardi, Rifardi (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2025)
Coral reefs play a role in maintaining marine biodiversity by providing habitat for various aquatic organisms, including reef fish from the Pomacentridae family. This study aims to analyze the relationship between coral reef cover and the Abundance of Pomacentridae reef fish in the waters of Setan Island, West Sumatra. The underwater photo transect (UPT) method is employed for coral cover analysis, while the underwater visual census (UVC) method is utilized for collecting fish abundance data. The results showed that the average percentage value of coral reef cover at a depth of 3 m was 20.38%, and at a depth of 6 m, it was 17.51%, indicating a poor category for the percentage value of coral reef cover. Data collection was conducted at four different stations. The highest coral cover was recorded at Station I (31.35%), while the lowest was at Station IV (0.33%). The Abundance of Pomacentridae reef fish varied between stations, with the highest Abundance observed in areas with higher coral cover. Based on simple linear regression analysis, the percentage of live coral cover accounts for 56.19% of the variation in the abundance value of Pomacentridae coral fish (R² = 0.5619), with a strong correlation (r = 0.7496). This indicates that declining coral reef conditions can harm fish populations. This finding underscores the significance of coral reef conservation efforts in maintaining marine biodiversity and ecosystem balance